Multi-Scale Vision-Language Foundation Model for Explainable Lung Cancer Risk Assessment from CT Imaging and Nodule Segmentation - Richard Bage; Pierre Webb (International Journal of Clinical and Translational Medicine, 2026)
Lung cancer remains a leading cause of cancer mortality worldwide, and low-dose computed tomography screening has demonstrated mortality reduction through early detection. However, current computer-aided diagnosis systems often operate as opaque classifiers that provide inadequate explanations for clinical decision-making. This paper presents a multi-scale vision-language foundation model that integrates CT imaging with natural language radiology reports to deliver explainable risk assessments through structured textual justifications. The architecture combines a hierarchical vision encoder that captures nodule morphology across multiple spatial resolutions with a cross-modal alignment module that maps visual features to a domain-adapted language space. We discuss system-level design choices including the trade-offs between fine-grained segmentation accuracy and global context preservation, the challenges of aligning radiological semantics across institutions, and the infrastructure required for clinical deployment. The model employs a multi-stage training pipeline that leverages both supervised nodule segmentation and weakly supervised vision-language pre-training on large-scale chest CT-report pairs. Explainability is achieved through attention-based visual grounding and generated textual descriptions that highlight salient imaging findings, nodule characteristics, and risk-relevant features. We analyze governance and fairness implications arising from training data biases, demographic shifts, and the regulatory frameworks governing AI-assisted radiology. Robustness to scanner variability, population heterogeneity, and adversarial perturbations is examined alongside sustainability considerations for computational efficiency. We argue that vision-language foundation models can transform lung cancer screening programs by providing interpretable, evidence-based risk communication, but only if their design is accompanied by rigorous validation protocols and continuous monitoring in real-world clinical workflows.